Un parcours éditorial au service des sciences humaines - Marie-Luce Rauzy (Tracés, 2018)
The author returns to a professional career path in the publishing of the humanities and social sciences, from the publication of a dictionary to that of a scientific journal in paper and digital format. This path is part of a profoundly changing technical and economic context: while school publishing remains flourishing, driven by the needs defined by the Ministry of National Education, university publishing became more fragile at the end of the 1990s in a context of exponential growth in subscription costs charged by commercial publishers, leading to a gradual reduction in institutional acquisitions. This involves in particular the publication of small scientific journals. Initiatives were then launched to develop digital publishing, initially in an uncoordinated way. The author’s journey allows us to trace in the singular the history of the transformation of editorial models and the role played by the various actors in research.